2019
DOI: 10.14744/bej.2019.63835
|View full text |Cite
|
Sign up to set email alerts
|

Clinical use of Dexamethasone Implants in Resistant Macular Edema Secondary to Branch Retinal Vascular Occlusion compared with Intravitreal Anti-Vascular Endothelial Growth Factor

Abstract: Branch retinal vein occlusion (BRVO) is the second most common type of retinal vascular disorder. Both inflammation and increased vascular endothelial growth factor (VEGF) levels play important roles in the pathogenesis of macular edema (ME) secondary to BRVO. The aim of this study was to compare the efficacy of 0.7-mg intravitreal dexamethasone implants with continued anti-VEGF treatment in patients with ME secondary to BRVO who were poor responders to at least 6 previous anti-VEGF injections. Methods: Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…[18] Several studies have shown that ITA is a safe option as it has rare rise in IOP that is usually transient and easy to control [19], [21], [30]- [33], similar to our study.…”
Section: Complicationssupporting
confidence: 89%
“…[18] Several studies have shown that ITA is a safe option as it has rare rise in IOP that is usually transient and easy to control [19], [21], [30]- [33], similar to our study.…”
Section: Complicationssupporting
confidence: 89%
“…In the MEAD study, cataract related to a single injection did not develop, and 70% of cataracts developed after four injections (19). Similarly, in another study, Eris et al (20) reported that during the 6 months of follow-up after a single dose of DEX for the treatment of BRVO, no patient developed cataract. The reason for the absence of cataract in our study may be that a single DEX implant was applied.…”
Section: Discussionmentioning
confidence: 87%
“…At baseline the median IOP was 14 (9-20) mmHg in the DEX group and 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) in the RAN group (p=0.518). Figure 3 shows the median IOP alteration in each group over time.…”
Section: Resultsmentioning
confidence: 95%